Tata Kelola Pasar Tradisional Pasca Relokasi di Kabupaten Muaro Jambi - Sela Ulandari; M. Yusuf; Azira Novia Rizal (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
Traditional markets are an important component of the people’s economy and play a strategic role in supporting trading activities and community social life. The Government of Muaro Jambi Regency implemented a policy to relocate the Sengeti People’s Market to reorganize and improve the quality of trading facilities so they become more orderly, feasible, and representative. However, after relocation, market utilization has not functioned optimally, and various management problems persist. This study aims to analyze traditional market governance after relocation in Muaro Jambi Regency, using the Sengeti People’s Market as a case study. The research employs a qualitative approach with a case study method. Data were collected through field observations, in-depth interviews, and documentation, involving informants from the Trade Division of the Office of Cooperatives, SMEs, Industry, and Trade, as well as market managers, traders, and community members. Data analysis was conducted using descriptive qualitative techniques, including data reduction, data presentation, and conclusion drawing. The findings show that post-relocation governance has not been optimally implemented. Key issues include weak policy communication, mismatches between facilities and traders’ needs, limited trader participation, and poor coordination among relevant agencies. The study highlights that successful market relocation depends not only on physical development but also on participatory, transparent, and sustainable governance, supported by stronger institutional coordination, increased trader involvement, and continuous evaluation.